2020
DOI: 10.1186/s12961-020-00627-4
|View full text |Cite|
|
Sign up to set email alerts
|

Self-care and remote care during pregnancy: a new paradigm?

Abstract: Self-care interventions and remote care offer innovative and equitable ways to strengthen access to sexual and reproductive health services. Self-isolation during COVID-19 provided the opportunity for obstetric facilities and healthcare providers to integrate and increase the usage of interventions for self-care and remote care for pregnant women and to improve the quality of care overall.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
21
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 7 publications
(7 reference statements)
1
21
0
1
Order By: Relevance
“…As a result of the pandemic, telehealth, a form of remote care [ 24 ], was widely implemented, and was experienced by women in this study as impersonal and incomplete. The limitations of telehealth were of significant concern to women and left some women feeling unable to share difficult conversations and being unsure of what concerns they needed to raise with their care provider.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…As a result of the pandemic, telehealth, a form of remote care [ 24 ], was widely implemented, and was experienced by women in this study as impersonal and incomplete. The limitations of telehealth were of significant concern to women and left some women feeling unable to share difficult conversations and being unsure of what concerns they needed to raise with their care provider.…”
Section: Discussionmentioning
confidence: 99%
“…When individuals assume responsibility for their own health and well-being with or without the support of a healthcare provider it is known as self-care [ 24 ]. Whilst self-care and remote care have been proposed as potential ways to improve overall quality of pregnancy care [ 24 ], these forms of care were implemented hastily during the pandemic in Australia without the provision of self-monitoring equipment to women.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…During the COVID-19 pandemic, telehealth services for mental health treatment and prenatal care have expanded tremendously. Relevant technologies have been adapted to ensure high-quality, evidence-based, remote care [ 71 , 72 ]. The acceptability of online care delivery platforms by clients, providers, and insurers has opened-up new possibilities for treatment and care in the perinatal period.…”
Section: Discussionmentioning
confidence: 99%
“…Tripp et al [17] investigated pregnancy-related applications and their impact on prenatal care; they showed that pregnancy-related applications can greatly help mothers in self-care while also improving mothers' and fetuses' health. Studies have also emphasized the significance of self-care during pregnancy [18,19] and/or during the outbreak of the COVID-19 pandemic [5,13]. e benefits of pregnancy self-care [12], the nature of pregnancy-related applications [17], the effects of education on improving pregnancy self-care processes [20], and the evaluation of self-care strategies for women with GDM during COVID-19 [11] have all been examined in studies on pregnancy during the COVID-19 pandemic; still, it seems that no study has been conducted to develop a COVID-19 self-care application for pregnant women.…”
Section: Introductionmentioning
confidence: 99%